Adhesion force measuring device for measuring interfacial adhesion force between an electrode and a separator and adhesion force measuring method using the same
The adhesion measuring device and method simulate the wet state conditions within secondary batteries to accurately measure the interface adhesion between electrodes and separation membranes, addressing the limitations of existing methods and improving battery performance and safety.
Patent Information
- Application Number
- JP2024552270
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-02
- Filing Date
- 2023-10-30
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-10-30
AI Technical Summary
Existing methods for evaluating the interface adhesion between electrodes and separation membranes in secondary batteries are inadequate, as they cannot accurately replicate the wet state conditions within the battery, leading to unreliable adhesion measurements.
An adhesion measuring device and method that simulates the actual state within a secondary battery by immersing the electrode and separation membrane measurement specimens in an electrolyte solution, allowing for the measurement of interfacial adhesion in a wet state.
This approach enables accurate and reliable measurement of the interface adhesion between electrodes and separation membranes, improving the prediction of adhesion changes within actual secondary batteries and enhancing battery performance and safety.
Smart Images

Figure 2025507926000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0144739 dated November 2, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to an adhesion measuring device for measuring the interfacial adhesion between an electrode and a separator, and a method for measuring adhesion using the same. [Background technology]
[0003] In recent years, the depletion of fossil fuels has led to rising energy prices and growing concern over environmental pollution, making the demand for environmentally friendly alternative energy sources an essential factor for the future of life. Accordingly, research into various power generation technologies, such as atomic, solar, wind, and tidal power, has been ongoing, and there has also been great interest in power storage devices to use the energy produced in this way more efficiently.
[0004] In particular, as technological development and demand for mobile devices increases, the demand for batteries as an energy source is rapidly increasing, and research is being conducted into batteries that can meet various requirements.
[0005] Typically, in terms of battery shape, there is a high demand for square-type secondary batteries and pouch-type secondary batteries that are thin and can be applied to products such as mobile phones, and in terms of materials, there is a high demand for lithium secondary batteries such as lithium ion batteries and lithium ion polymer batteries that have advantages such as high energy density, discharge voltage, and output stability.
[0006] In general, such a secondary battery has an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between them, which is built into a battery case, and the positive and negative electrode tabs are welded to two electrode tabs and sealed to be exposed to the outside of the battery case. These electrode tabs are in contact with an external device and electrically connected, and the secondary battery supplies power to the external device or is supplied with power from the external device through the electrode tabs.
[0007] Ensuring safety during the manufacture and use of secondary batteries is an important issue to be resolved. In particular, separators commonly used in secondary batteries tend to fold due to their material characteristics and various reasons in the manufacturing process, which can cause stability problems such as internal short circuits at the folded parts of the separator.
[0008] FIG. 1 is a photograph showing an electrode assembly in which folding has occurred on the surface of a separator.
[0009] Referring to FIG. 1, it can be seen that the separator and electrode interface peel off due to the flow of the electrode assembly stacked inside the battery case after the electrolyte is injected during the manufacturing process of the secondary battery, and the separator is folded. In this way, an internal short circuit occurs in the folded portion of the separator, which not only reduces the voltage efficiency by inducing low voltage, but also leads to stability problems such as deterioration. Meanwhile, in order to increase the adhesive strength between the electrode and the separator, a process such as lamination or heat pressing of the electrode and the separator may be performed, but in this case, excessive drying may cause lithium plating on the negative electrode, thereby deteriorating the battery performance. Therefore, an evaluation of the interfacial adhesive strength between the electrode and the separator is required in the physical property evaluation process performed during the manufacturing process of the secondary battery.
[0010] Conventionally, to evaluate the interfacial adhesion between the electrode and the separator, the electrode and separator on which the electrode composite layer was formed were cut to a certain size, the electrode and the separator were overlapped, and a PET film was sandwiched between them, and a test specimen was manufactured by heating and pressing them with a flat press, and the electrode and the separator were separated using UTM (Universal Testing Machine) equipment to evaluate the adhesion. However, in this case, the measurement was performed in a dry state, making it difficult to judge the adhesion level between the electrode and the separator wetted with electrolyte inside the actual secondary battery, and the measurement results showed higher adhesion than the results measured in a wet state with the actual electrolyte, making it difficult to utilize the measured value.
[0011] In addition, even when measuring the adhesive strength between an electrode and a separator obtained by disassembling an actual secondary battery in order to evaluate the adhesive strength between the electrode and the separator in a wet state, there is a problem that the electrolyte impregnated in the obtained electrode and separator volatilizes during the measurement time after disassembly, leading to a result that differs from the actual level.
[0012] Therefore, in order to more accurately evaluate the interfacial adhesion between the electrodes and the separator in a secondary battery process, it is necessary to develop a technology that can measure the adhesion of the electrodes by replicating the electrode conditions inside an actual secondary battery. Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention has been made to solve the above-mentioned problems, and aims to provide an apparatus for evaluating the adhesive strength between an electrode and a separator in an environment equivalent to the conditions inside an actual secondary battery in which the electrode and separator are immersed in an electrolyte, and an adhesive strength measuring method using the same. [Means for solving the problem]
[0014] The present invention provides an adhesion measuring device for measuring the interfacial adhesion between an electrode and a separator. In one embodiment, the adhesion measuring device according to the present invention includes a fixture having a space for placing a test specimen including an electrode and a separator, and an electrolyte solution is contained in the space to fix the test specimen supported in the electrolyte solution, and an adhesion strength measuring device having a grip for holding an end region of the separator of the test specimen and pulling the held separator in a direction perpendicular to the electrode surface to measure the force at which the separator is separated from the electrode, and a part of the upper surface of the fixture is recessed downward to form a receiving portion for receiving the electrolyte solution, and the test specimen is supported in the electrolyte solution contained in the receiving portion to measure the interfacial adhesion between the electrode and the separator in a wet state.
[0015] In a specific example according to the present invention, the fixing jig has a structure including a lid for sealing an open portion of the container so as to prevent the electrolyte contained in the container from volatilizing.
[0016] In addition, the fixing jig includes a first fixing protrusion that protrudes upward from an upper surface and is bent inward, and a first guide groove that is formed between a bottom surface of the first fixing protrusion and the upper surface of the fixing jig, and a cover is inserted into an open end of the first guide groove in a sliding manner, so that the open space of the receiving part is sealed or opened / closed.
[0017] In another specific example according to the present invention, the accommodating section includes a second fixing protrusion formed on a side surface protruding inwardly, and a second guide groove formed between a bottom surface of the second fixing protrusion and a bottom surface of the accommodating section, the second fixing protrusion and the second guide groove each including a pair of second fixing protrusions and a pair of second guide grooves arranged facing each other in the width direction of the accommodating section, and a test specimen is inserted in a sliding manner into the open ends of the pair of second guide grooves.
[0018] The receiving portion is structured so that the ratio of the length between the pair of second fixing projections to the width direction length of the region where no second fixing projections are formed is in the range of 0.7 to 0.85.
[0019] The accommodating portion has a structure in which the length in the width direction of the region in which the second guide grooves are not formed is greater than the length between the pair of second guide grooves.
[0020] In another embodiment of the present invention, the fixing jig is connected to the cover by a hinge so that the open space of the receiving part is closed or opened by rotating the cover.
[0021] In another embodiment of the present invention, the adhesion measuring device further includes a detector that detects and displays a force at which the electrode of the test specimen and the separator are separated from each other.
[0022] The present invention also provides an adhesion measuring method for measuring the interfacial adhesion between an electrode and a separator in a wet state using the above-mentioned adhesion measuring device.
[0023] In one embodiment according to the present invention, the method includes the steps of placing a test specimen in a fixture containing an electrolyte to support the test specimen in the electrolyte, fixing an end of a separator of the test specimen supported in the electrolyte to a grip of an adhesion strength tester, and operating the adhesion strength tester to separate the electrode and separator of the test specimen supported in the electrolyte and measure the interfacial adhesion between the electrode and separator in a wet state.
[0024] In a specific embodiment according to the present invention, the test specimen includes a positive electrode or a negative electrode and a separator obtained by disassembling a secondary battery.
[0025] In another specific embodiment according to the present invention, the electrolyte has the same components as the electrolyte stored inside the disassembled secondary battery.
[0026] In another specific embodiment of the present invention, the secondary battery is a secondary battery that has undergone an activation process.
[0027] In another embodiment according to the present invention, the step of placing the test specimen in a fixture containing an electrolyte and supporting the test specimen in the electrolyte includes attaching a double-sided adhesive tape to an electrode surface of the test specimen, and supporting the test specimen attached to the glass substrate in the electrolyte while the test specimen with the double-sided adhesive tape attached to the glass substrate is attached to the surface of the glass substrate.
[0028] In another embodiment according to the present invention, the step of placing the test specimen in a fixture containing an electrolyte and supporting the test specimen in the electrolyte includes a process of covering the fixture with a lid to prevent the electrolyte contained in the fixture from volatilizing during a waiting time for the test specimen supported in the electrolyte to be impregnated with a sufficient amount of electrolyte. Effect of the Invention
[0029] The adhesion measuring device and adhesion measuring method using the same of the present invention have the advantage that it is possible to replicate the internal condition of a secondary battery containing an actual electrolyte, easily measure the interfacial adhesion between an electrode and a separator in an environment equivalent to that inside an actual secondary battery, and predict the interfacial adhesion between an electrode and a separator inside an actual secondary battery. [Brief description of the drawings]
[0030] [Figure 1] 1 is a photograph showing the folding of a separator obtained by disassembling a conventional secondary battery. [Diagram 2] 1 is a perspective view showing an adhesive strength measuring device according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a plan view showing a fixing jig according to an embodiment of the present invention. [Figure 4] 4 is a cutaway view showing a cross section of the fixing jig taken along the line AA' of FIG. 3. [Diagram 5] FIG. 2 is a perspective view showing a connection between a fixing jig and a lid according to an embodiment of the present invention. [Figure 6] FIG. 11 is a perspective view showing a connection between a fixing jig and a lid according to another embodiment of the present invention. [Figure 7]1 is a graph showing the results of measuring the adhesive strength between a separator and a negative electrode or a positive electrode with or without electrolyte impregnation. [Figure 8] 1 is a graph showing the results of measuring the adhesive strength between a negative electrode and a separator at each process step. [Figure 9] 1 is a flow chart showing the flow of a method for measuring the interfacial adhesion between an electrode and a separator in a wet state. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Since the present invention can be modified in various ways and can have various forms, specific embodiments are illustrated in the drawings and described in detail in the text, but this is not intended to limit the present invention to the specific disclosed forms, and it is understood that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.
[0032] In this application, the terms "comprise" and "have" are intended to specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, and may be understood as not precluding the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof. In addition, when a part such as a layer, film, region, or plate is described as being "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part in between. Conversely, when a part such as a layer, film, region, or plate is described as being "under" another part, this includes not only the case where it is "directly under" the other part, but also the case where there is another part in between. In addition, in this application, being "on" may include not only the case where it is located on the top, but also the case where it is located on the bottom.
[0033] The present invention provides an adhesion measuring device for measuring the interfacial adhesion between an electrode and a separator, and an adhesion measuring method using the same.
[0034] Typically, the method of measuring the adhesion between the electrode and the separator is to cut the electrode and separator with the electrode composite layer formed thereon to a certain size, then stack the electrode and the separator, sandwich a PET film between them, and heat and press them with a flat press to produce a test specimen. The electrode and the separator are then separated using a Universal Testing Machine (UTM) to measure the adhesion.
[0035] However, in this case, the measurement was performed in a dry state, and it was difficult to determine the level of adhesion between the electrode and the separator wetted with an electrolyte inside an actual secondary battery. The measurement results showed a higher adhesion than the results measured in a wetted state with an actual electrolyte, making it difficult to utilize the measurement results.
[0036] In addition, even when measuring the adhesive strength between an electrode and a separator obtained by disassembling an actual secondary battery in order to evaluate the adhesive strength between the electrode and the separator in a wet state, there is a problem that the electrolyte impregnated in the obtained electrode and separator volatilizes during the measurement time after disassembly, leading to a result that differs from the actual level.
[0037] Therefore, in order to more accurately evaluate the interfacial adhesion between the electrodes and the separator in a secondary battery process, it is necessary to develop a technology that can measure the adhesion of the electrodes by replicating the electrode condition inside an actual secondary battery.
[0038] Therefore, in order to solve the above problems, the present invention provides an apparatus for evaluating the adhesive strength between an electrode and a separator in an environment equivalent to the condition inside an actual secondary battery in which the electrode and separator are immersed in an electrolyte, and an adhesive strength measuring method using the same.
[0039] Hereinafter, an adhesion measuring device for measuring the interfacial adhesion between an electrode and a separator according to the present invention and an adhesion measuring method using the same are provided.
[0040] 2 is a perspective view showing an adhesive strength measuring device according to an embodiment of the present invention. Referring to FIG. 2, the adhesive strength measuring device 1 according to the present invention includes a fixture 10 having a space for placing a test specimen 30 including an electrode 31 and a separator 32, and containing an electrolyte in the space to fix the test specimen 30 supported in the electrolyte, and an adhesive strength measuring device 20 having a grip 21 for holding an end region of the separator 32 of the test specimen 30 and pulling the held separator 32 in a direction perpendicular to the surface of the electrode 31 to measure the force at which the separator 32 is separated from the electrode 31, and a part of the upper surface of the fixture 10 is recessed downward to form a receiving portion 11 for receiving an electrolyte, and the test specimen 30 is supported in the electrolyte contained in the receiving portion 11, and the interfacial adhesive strength between the electrode 31 and the separator 32 in a wet state is measured.
[0041] In the present invention, the "test specimen 30" refers to an object to be measured using the adhesion measuring device 1 according to the present invention, and specifically may be an electrode 31 assembly. The electrode 31 assembly may include an electrode 31 on which an electrode 31 mixture layer is formed, and a separator 32, and the electrode 31 may be a positive electrode or a negative electrode on which an electrode 31 mixture layer is formed on one or both sides of an electrode 31 current collector.
[0042] The fixture 10 may have a receiving section 11 having a space in which the test specimen 30 to be measured can be placed. The receiving section 11 may be a space formed by a part of the upper surface of the fixture 10 being indented downward. The indented space means a space in which the test specimen 30 can be placed and an electrolyte can be stored, and the receiving section 11 may be formed to a predetermined depth so that the electrolyte can be stored therein and the test specimen 30 can be sufficiently impregnated with the electrolyte. The fixture 10 may be formed of various types of metal, for example, carbon steel, stainless steel, aluminum or alloys thereof, and is not limited to a particular metal.
[0043] Meanwhile, the adhesive strength measuring device 20 includes a grip 21 capable of gripping an end of the separation membrane 32 of the test specimen 30, and the gripped separation membrane 32 is pulled in one direction to measure the force required to separate the separation membrane 32 from the electrode 31. The adhesive strength measuring device 20 is a general universal testing machine (UTM), and may be, for example, a peel-off testing machine. In a specific example, in order to measure the interfacial adhesive force between the electrode 31 and the separation membrane 32 of the test specimen 30, the electrode 31 and the separation membrane 32 in a part of the test specimen 30 are artificially separated, and then the end of the separation membrane 32 separated from the electrode 31 is fixed by the grip 21 of the adhesive strength measuring device 20, and pulled at an angle of 90° to the surface of the electrode 31 to measure the force required to peel the separation membrane 32 from the electrode 31 (90° peel-off test).
[0044] In addition, the grip 21 of the adhesive strength measuring device 20 may include a metal jaw face having a grid formed on its surface. In the process of operating the adhesive strength measuring device 20, a phenomenon may occur in which the separation film 32 slips while being pressed by the grip 21. Therefore, by forming a grid on the jaw face of the grip 21, the fixing force of the grip 21 to the separation film 32 can be increased. The metal jaw face may be formed of various types of metal, for example, carbon steel, stainless steel, aluminum, or alloys thereof. In addition, the metal jaw face may have a lattice pattern having intaglio or relief on its surface, and the width and length of the lattice pattern, the recessed depth of the intaglio, or the protruding height of the relief, etc., are not particularly limited and may have various lengths.
[0045] FIG. 3 is a plan view showing a fixture according to an embodiment of the present invention, and FIG. 4 is a cutaway view showing a cross section of the fixture shown in FIG. 3 cut in the A-A' direction. Referring to FIGS. 3 and 4, the fixture 10 may have a structure including a lid 40 for sealing an open portion of the receiving portion 11 to prevent the electrolyte contained in the receiving portion 11 from volatilizing. In a specific example, the test specimen 30 obtained by disassembling a secondary battery may differ from the situation inside the secondary battery because a time interval is formed between when the secondary battery is disassembled and when it is placed in the receiving portion 11 of the fixture 10 containing the electrolyte, and the electrolyte may volatilize into the air during the time interval. In this case, in order to realize a situation equivalent to the inside of a secondary battery, the electrode 31 specimen may be supported in the electrolyte for a certain period of time, and a sufficient waiting time may be required so that the electrolyte can be sufficiently impregnated into the electrode 31 specimen. However, during the waiting time, the electrolyte contained in the receiving portion 11 of the fixture 10 may evaporate into the air, which may cause a problem that the electrode 31 specimen is not sufficiently wetted. To prevent this, the open portion of the receiving portion 11 of the fixture 10 may be sealed with a lid 40 to prevent the electrolyte from evaporating.
[0046] Fig. 5 is a perspective view showing a combination of a fixing jig and a cover according to an embodiment of the present invention. Referring to Fig. 5, the fixing jig 10 includes a first fixing protrusion 12 formed by protruding upward from an upper surface and bending inward, and a first guide groove 13 formed between a bottom surface of the first fixing protrusion 12 and an upper surface of the fixing jig 10, and a cover is inserted into an open end of the first guide groove 13 in a sliding manner, so that the open space of the receiving part 11 is sealed or opened / closed.
[0047] For example, the first fixing protrusion 12 may protrude upward from the upper surface of the fixing jig 10 in an area where the accommodating portion 11 is not formed, and may be bent inward to have a " shape. The bottom surface of the first fixing protrusion 12 has a certain step with the upper surface of the fixing jig 10, and a first guide groove 13 may be formed between the bottom surface of the first fixing protrusion 12 and the upper surface of the fixing jig 10. The depth of the first guide groove 13 corresponds to the length of the bent end portion of the first fixing protrusion 12, and is not limited to a certain depth.
[0048] Meanwhile, the first fixing protrusion 12 and the first guide groove 13 have a pair structure arranged facing each other in parallel in the width direction of the fixing jig 10, and a cover is structured to be detachable in a sliding manner on the open end of the first guide groove 13, so that the open space of the accommodating section 11 can be sealed or opened / closed.
[0049] FIG. 6 is a perspective view showing a combination of a fixing jig and a cover according to another embodiment of the present invention. Referring to FIG. 6, the fixing jig 10 may have a structure in which the cover is connected to the fixing jig 10 through a hinge 41, and the open space of the receiving part 11 is sealed or opened by rotating the cover. The hinge 41 is not limited to a hinge 41 having a specific structure, and may be a hinge 41 including a first strand and a second strand that can be relatively rotated based on a virtual rotation axis. For example, the first strand is connected to a side of the fixing jig 10, and the second strand is connected to the cover, and the first strand and the second strand are relatively rotated, and the open space of the receiving part 11 of the fixing jig 10 is sealed or opened. In addition, the number of hinges 41 connecting the fixing jig 10 and the cover is not limited to a specific number, but it is preferable that the fixing jig 10 and the cover are connected to each other through two or more hinges 41 in consideration of the binding force between the fixing jig 10 and the cover.
[0050] In another embodiment of the present invention, the receiving part 11 includes a second fixing protrusion 14 formed on a side surface protruding inward, and a second guide groove 15 formed between a bottom surface of the second fixing protrusion 14 and a bottom surface of the receiving part 11, and the second fixing protrusion 14 and the second guide groove 15 include a pair of second fixing protrusions 14 and a pair of second guide grooves 15 arranged facing each other in the width direction of the receiving part 11, and the test specimen 30 may be inserted in a sliding manner into the open ends of the pair of second guide grooves 15. In the process of measuring the interfacial adhesive strength between the electrode 31 and the separation film 32 of the electrode 31 specimen, the separation film 32 is peeled off from the electrode 31 while the end of the separation film 32 is held by the grip 21 of the adhesion strength measuring device 20 and the separation film 32 is pulled at an angle of 90° with respect to the surface of the electrode 31. At this time, if the electrode 31 specimen is not fixed, when the separation membrane 32 is separated from the electrode 31, the electrode 31 may move together with the separation membrane 32, making it difficult to perform accurate measurement. Therefore, the receiving part 11 is provided with a separate second fixing protrusion 14 and a second guide groove 15, and the test specimen 30 is inserted into the second guide groove 15 to be bound, so that the electrode 31 can be fixed so as not to move together with the separation membrane 32 when the separation membrane 32 is separated from the electrode 31 by the adhesion strength measuring device 20. At this time, it is necessary to manufacture the test specimen 30 such that the widths of the electrode 31 and the separation membrane 32 are different from each other so that only the electrode 31 of the test specimen 30 straddles the second fixing protrusion 14 and the separation membrane 32 of the test specimen 30 does not straddle the second fixing protrusion 14.
[0051] 3 and 4, the accommodating portion 11 may be structured such that the ratio w' of the length between a pair of second fixing protrusions to the widthwise length w of the area in which the second fixing protrusions 14 are not formed is in the range of 0.7 to 0.85.
[0052] If the ratio of the width w' of the receiving portion 11 in which the second fixing protrusions 14 are formed to the width w of the region in which the second fixing protrusions 14 of the receiving portion 11 are not formed is greater than 0.85, the electrode 31 of the test specimen 30 will not sufficiently straddle the second fixing protrusions 14, and if it is less than 0.7, the ratio will be smaller than the width of the separation membrane 32 of the test specimen 30, and an additional process of cutting the separation membrane 32 may be required.
[0053] Meanwhile, in another specific example of the present invention, the receiving section 11 may have a structure in which the widthwise length w of the region where the second guide grooves 15 are not formed is greater than the length w'' between the pair of second guide grooves 15. After the test specimen 30 is placed in the space of the receiving section 11 where the second guide grooves 15 are not formed, the test specimen 30 is pushed into the space where the pair of second guide grooves 15 are formed, and the test specimen 30 is slid and moved, so that the test specimen 30 is inserted into the second guide grooves 15. In order to fix the test specimen 30 inserted into the second guide grooves 15 so as not to swing left and right, the length w'' between the pair of second guide grooves 15 may be formed to be the same as the width of the test specimen 30. In contrast, the space in the storage section 11 where the second guide grooves 15 are not formed is a space in which the test specimen 30 is placed before being inserted between the pair of second guide grooves 15, and is intended to allow an operator to easily place the test specimen 30 in the space where the second guide grooves 15 are not formed while holding the test specimen 30, and the widthwise length w of the area where the second guide grooves 15 are not formed can be formed to be larger than the widthwise length of the test specimen 30. Therefore, the length w'' between the pair of second guide grooves 15 is set to the same length as the widthwise length of the test specimen 30 so that the test specimen 30 inserted between the pair of second guide grooves 15 is fixed, while the widthwise length w of the storage section 11 where the second guide grooves 15 are not formed is formed to be longer than the length between the pair of second guide grooves 15 so that an operator can easily place the test specimen 30 in the storage section 11 while holding the test specimen 30.
[0054] The adhesion measuring device 1 may further include a detection unit (not shown) that detects and displays the force at which the electrode 31 of the test specimen 30 and the separation film 32 are separated. The detection unit may display the interfacial adhesion force between the electrode 31 of the test specimen 30 and the separation film 32 as a numerical value. This may be a structure provided in the adhesion strength measuring device 20.
[0055] Also, the adhesion measuring device 1 may further include a storage unit (not shown). The storage unit may receive and store interfacial adhesion measurement data between the electrode 31 and the separator 32 of the test specimen 30. If necessary, the storage unit may further include a function of storing the measurement results classified into various types, such as the types, thicknesses, and ratios of the metal collector, the electrode 31, the mixture layer, and the separator 32, in a database. As a result, it is possible to predict the possibility of the separator 32 folding due to a decrease in adhesion between the electrode 31 and the separator 32 inside an actual secondary battery and the resulting internal short circuit, based on the data stored in the database.
[0056] The present invention also provides a method for measuring the interfacial adhesion between an electrode and a separator in a wet state, using the above-mentioned adhesion measuring device.
[0057] 9 is a flow chart showing a method for measuring the interfacial adhesion between an electrode and a separator in a wet state according to an embodiment of the present invention. Referring to FIG. 9, the method for measuring the interfacial adhesion between an electrode and a separator in a wet state according to the present invention includes the steps of placing a test specimen in a fixture containing an electrolyte and supporting the test specimen in the electrolyte (S10), fixing an end of the separator of the test specimen supported in the electrolyte to a grip of an adhesion strength tester (S20), and operating the adhesion strength tester to separate the electrode and separator of the test specimen supported in the electrolyte and measure the interfacial adhesion between the electrode and the separator in a wet state (S30).
[0058] First, the step of supporting the test specimen in the electrolyte (S10) refers to a step of placing the test specimen including the electrodes and the separator in a receiving part containing the electrolyte so that the electrolyte can be impregnated into the test specimen. This includes the case where the test specimen is placed in the receiving part while the receiving part contains the electrolyte, and the case where the test specimen is placed in the receiving part and then received in the electrolyte. That is, this means that the electrolyte can be placed in the receiving part before or after the test specimen is placed in the receiving part. Meanwhile, it is preferable to pour in a sufficient amount of electrolyte so that the test specimen placed in the receiving part can be impregnated with the electrolyte.
[0059] Furthermore, the test specimen to be placed in the receiving section may be placed by itself, or, if necessary, a double-sided adhesive tape may be attached to the electrode surface of the test specimen, and the test specimen attached to the glass substrate with the double-sided adhesive tape attached to the surface of the glass substrate may be supported in the electrolyte. The process of adhering the electrode specimen to the glass substrate may be performed by applying pressure with a roller about 5 to 10 times after the test specimen is attached to the glass substrate.
[0060] Meanwhile, the test specimen must be fixed so that it does not move in the left-right or up-down direction during the process of measuring the adhesive strength using an adhesive strength tester. As described above, the test specimen can be inserted and fixed into a pair of second guide grooves located inside the receiving part. Specifically, when the receiving part is divided into a region in which a pair of second guide grooves is formed and a region in which it is not formed in the longitudinal direction, an operator can position the test specimen in the region in which the pair of second guide grooves is not formed in the receiving part and then push it between the pair of second guide grooves to fix the test specimen in such a way that the test specimen is inserted into the pair of second guide grooves.
[0061] In addition, the step of placing the test specimen in the electrolyte (S10) may include a step of waiting for a certain time so that the test specimen placed in the electrolyte can be impregnated with a sufficient amount of electrolyte. In this case, during the waiting time, the step of covering the fixture with a lid may be included so that the electrolyte contained in the fixture does not volatilize. After the test specimen is obtained by disassembling the secondary battery, the electrolyte impregnated in the test specimen may be exposed to the air and volatilize while being transferred to a container containing the electrolyte, and a waiting time for placing the test specimen in the electrolyte for a sufficient time may be required to replenish the volatilized electrolyte. In this case, the step of covering the open portion of the container with a lid may be included so that the electrolyte contained in the container does not volatilize in the air and the electrolyte is not additionally supplied during the waiting time. In addition, when the open portion of the container is covered with a lid, the fixture can prevent the electrolyte contained in the container from overflowing due to being blocked by the lid even when the container is subjected to an external impact.
[0062] Meanwhile, in the step of supporting the test specimen in the electrolyte (S10), the test specimen may include a positive electrode or a negative electrode and a separator obtained by disassembling a secondary battery. The present invention aims to measure the interfacial adhesive strength between an electrode wetted with an electrolyte and a separator in order to solve the problem that the separator is folded due to a decrease in adhesive strength between the electrode and the separator inside an actual secondary battery after the electrolyte is injected into the electrode assembly contained in the battery case, and therefore the test specimen is characterized by being obtained by disassembling the electrode assembly contained in the battery case.
[0063] Meanwhile, the electrolyte contained in the container may have the same components as the electrolyte stored in the disassembled secondary battery. By setting the electrolyte contained in the container and the electrolyte contained in the secondary battery to have the same components, the same conditions as those in the actual secondary battery can be replicated, thereby improving the reliability of the measurement results.
[0064] Furthermore, the secondary battery is composed of a secondary battery that has undergone an activation process, and a test specimen can be obtained by disassembling the secondary battery that has undergone the activation process. In the manufacturing process of a secondary battery, when an activation process is performed, a volume flow of the secondary battery occurs due to charging and discharging, which causes a change in the interfacial adhesion between the electrode and the separator, and the separator may be folded. Therefore, the adhesive strength between the electrode and the separator of the test specimen obtained by disassembling various secondary batteries according to the presence or absence and the degree of the activation process can be measured, and the interfacial adhesion state between the electrode and the separator inside the secondary battery can be predicted based on the result before and after the activation step, or according to the degree of the activation step.
[0065] Meanwhile, in the present specification, "activation" refers to a process of supplying a certain amount of electricity to a secondary battery cell that does not have electrical characteristics, thereby causing the positive and negative electrodes to have electrical characteristics, and may be understood to include all reactions associated with the initial charging of the secondary battery cell. Non-limiting examples of reactions associated with the initial charging include formation of an SEI film, charging a portion of the battery capacity, and activation of the negative electrode such as lithiation of a carbon-based negative electrode active material.
[0066] Next, the present invention includes a step (S20) of fixing an end of the separator of the test specimen supported in the electrolyte to a grip of an adhesive strength tester. In order to fix the end of the separator of the test specimen supported in the electrolyte to the grip of the adhesive strength tester, a process of separating the separator from an electrode at one end of the test specimen may be performed in advance. The adhesive strength tester may be a general universal testing machine (UTM), and as one example, a peel-off testing machine. The grip of the adhesive strength tester may include a metal jaw face having a grid formed on its surface, and may prevent the separator fixed by the grip from slipping.
[0067] Next, the present invention may include a step (S30) of operating an adhesion strength tester to separate the electrode and the separator of the test specimen supported in the electrolyte, and measuring the interfacial adhesion between the electrode and the separator in a wet state.
[0068] As a specific example, to measure the interfacial adhesion between the electrode and the separator of the test specimen, the load of the adhesion strength meter is set to a zero base, the load speed is set to a range of 5 to 200 mm / min, and then the electrode and the separator in a certain region of the test specimen are artificially separated. In this state, the end of the separator separated from the electrode is fixed by the grip of the adhesion strength meter, and the adhesion strength meter is operated and pulled at an angle of 90° to the electrode surface to measure the force at which the separator is peeled off from the electrode (90° Peel-off test).
[0069] In addition, the method may include a process of creating a database of the results of measuring the interfacial adhesion between the electrodes and the separator, which may be classified into various types, thicknesses, and ratios of the metal collector, electrode mixture layer, and separator. Based on the data recorded in the database, it may be possible to predict the possibility of the separator folding due to a decrease in the adhesion between the electrode and the separator inside an actual secondary battery, and the resulting internal short circuit.
[0070] Meanwhile, the electrode of the present invention means a positive electrode or a negative electrode, and the positive electrode has a structure in which a positive electrode active material layer is laminated on one or both sides of a positive electrode current collector. In one example, the positive electrode active material layer includes a positive electrode active material, a conductive material, and a binder polymer, and may further include a positive electrode additive commonly used in the art as necessary.
[0071] The positive electrode active materials may be the same or different lithium-containing oxides. As the lithium-containing oxide, lithium-containing transition metal oxides may be used.
[0072] For example, lithium-containing transition metal oxides include Li x CoO2(0.5 <x<1.3)、Li x NiO2(0.5 <x<1.3)、Li xMnO2 (0.5 < x < 1.3), Li x Mn2O4 (0.5 < x < 1.3), Li x (Ni a Co b Mn c )O2 (0.5 < x < 1.3, 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), Li x Ni 1-y Co y O2 (0.5 < x < 1.3, 0 < y < 1), Li x Co 1-y Mn y O2 (0.5 < x < 1.3, 0 ≤ y < 1), Li x Ni 1-y Mn y O2 (0.5 < x < 1.3, 0 ≤ y < 1), Li x (Ni a Co b Mn c )O4 (0.5 < x < 1.3, 0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), Li x Mn 2-z Ni z O4 (0.5 < x < 1.3, 0 < z < 2), Li x Mn 2-z Co z O4 (0.5 < x < 1.3, 0 < z < 2), Li x CoPO4 (0.5 < x < 1.3), and Li x FePO4 (0.5 < x < 1.3), and can be any one selected from the group consisting of these or a mixture of two or more thereof. Further, the lithium-containing transition metal oxide can also be coated with a metal or metal oxide such as aluminum (Al). In addition to the lithium-containing transition metal oxide, one or more of sulfide, selenide, and halide can be used.
[0073] The positive electrode active material can be contained in the positive electrode active material layer in the range of 94.0 to 98.5% by weight. When the content of the positive electrode active material satisfies the above range, it is advantageous in terms of manufacturing a high-capacity battery and imparting sufficient conductivity of the positive electrode and adhesion between electrode materials.
[0074] The current collector used in the positive electrode may be any metal that is highly conductive and to which the positive electrode active material slurry can be easily attached, and is non-reactive within the voltage range of the electrochemical device.Specifically, non-limiting examples of the current collector for the positive electrode include foils made of aluminum, nickel, or a combination thereof.The positive electrode active material layer further includes a conductive material.
[0075] The binder polymer may be any binder commonly used in the art without limitation. For example, the binder may be a water-insoluble polymer that is soluble in an organic solvent and insoluble in water, or a water-soluble polymer that is insoluble in an organic solvent and soluble in water. The water-insoluble polymer may be one or more selected from the group including polyvinylidene fluoride (PVDF), polyvinylidene chloride (PVDC), polyacrylonitrile (PAN), polypropylene oxide (PPO), polyethylene oxide-propylene oxide copolymer (PEO-PPO), polytetrafluoroethylene (PTFE), polyimide (PI), polyetherimide (PEI), styrene butadiene rubber (SBR), polyacrylate, and derivatives thereof.
[0076] The water-soluble polymer may be one or more selected from the group including various cellulose derivatives such as carboxymethylcellulose (CMC), methylcellulose (MC), cellulose acetate phthalate (CAP), hydroxypropylmethylcellulose (HPMC), and hydroxypropylmethylcellulose phthalate (HPMCP).
[0077] The binder polymer content is proportional to the conductive material content in the upper and lower positive electrode active material layers, because it provides adhesive strength to the conductive material, which has a relatively small particle size compared to the active material, and because an increase in the conductive material content requires more binder polymer, whereas a decrease in the conductive material content requires less binder polymer.
[0078] The negative electrode has a structure in which a negative electrode active material layer is laminated on one or both sides of a negative electrode current collector. In one example, the negative electrode active material layer includes a negative electrode active material, a conductive material, a binder polymer, and the like, and may further include a negative electrode additive commonly used in the art, as necessary.
[0079] The negative electrode active material may include a carbon material, lithium metal, silicon, or tin. When a carbon material is used as the negative electrode active material, both low-crystalline carbon and high-crystalline carbon may be used. Typical low-crystalline carbons include soft carbon and hard carbon, and typical high-crystalline carbons include natural graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbons such as petroleum or coal tar pitch derived cokes.
[0080] Non-limiting examples of the current collector used in the negative electrode include foils made of copper, gold, nickel, copper alloys, or combinations thereof. The current collector may also be used by laminating a substrate made of the above materials.
[0081] The negative electrode may also include conductive materials and binders commonly used in the art.
[0082] The separator may be any porous substrate used in lithium secondary batteries, for example, a polyolefin-based porous membrane or nonwoven fabric, but is not limited thereto.
[0083] Examples of polyolefin-based porous membranes include membranes formed from polyolefin-based polymers such as polyethylene (high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene, etc.), polypropylene, polybutylene, polypentene, etc., either alone or as a mixture of these polymers.
[0084] Examples of nonwoven fabrics include polyolefin-based nonwoven fabrics, as well as nonwoven fabrics formed from polymers such as polyethylene terephthalate, polybutyleneterephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenyleneoxide, polyphenylenesulfide, and polyethylenenaphthalene, either alone or as a mixture of these.
[0085] The polymer may be a porous polymer and may be a polyvinylidene fluoride-based polymer. The polyvinylidene fluoride-based polymer may be polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, etc. acetatepropionate, cyanoethylpullulan, cyanoethylpolyvinylalcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan or carboxyl methyl cellulose, etc., may be used.
[0086] Also, an adhesive layer including electrosprayed polymeric fibers may be formed on one or both sides of the separator. The electroirradiated polymer fibers may be made of polyvinylidene fluoride (PVDF)-based polymers, styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyethylene glycol (PEG), polypropylene glycol (PPG), toluene diisocyanate (TDI), polymethylmethacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-co-vinyl acetate, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cellulose acetate butyrate, cellulose acetate propionate ... The polyolefin polymer may be one or a mixture of two or more selected from the group consisting of pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, and polyimide.
[0087] The structure of the nonwoven fabric can be a spunbond or meltblown nonwoven fabric made up of long fibers.
[0088] The thickness of the porous substrate is not particularly limited, but may be 5 to 50 μm. The pore size and pores present in the porous substrate are also not particularly limited, but may be 0.01 to 50 μm and 10 to 95%, respectively.
[0089] In order to improve the mechanical strength of the separator made of the porous substrate and to prevent short circuits between the positive electrode and the negative electrode, a porous coating layer including inorganic particles and a binder polymer may be further included on at least one surface of the porous substrate.
[0090] The electrolyte may include an organic solvent and an electrolyte salt, and the electrolyte salt is a lithium salt. The lithium salt may be any of those commonly used in non-aqueous electrolytes for lithium secondary batteries without limitation. For example, Li + The anion is F. - , Cl - , Br - , I - , NO 3- , N(CN) 2- , B.F. 4- , ClO 4- , AlO 4- , AlCl 4- , P.F. 6- , SbF 6- , AsF 6- , BF2C2O 4- , B.C.4O 8- , (CF3)2PF 4- , (CF3)3PF 3- , (CF3)4PF 2- , (CF3)5PF - , (CF3)6P - , CF3SO 3- , C4F9SO 3- , CF3CF2SO 3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH -, (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO 3- , CF3CO 2- , CHCO 2- , SCN - and (CF3CF2SO2)2N - It may include at least one selected from the group consisting of:
[0091] The organic solvent contained in the above-mentioned electrolytic solution may be any organic solvent commonly used in secondary battery electrolytic solutions, and may be used without limitation, for example, ethers, esters, amides, linear carbonates, cyclic carbonates, etc., each of which may be used alone or in combination of two or more. Among these, representative carbonate compounds may include cyclic carbonates, linear carbonates, or mixtures thereof.
[0092] Specific examples of cyclic carbonate compounds include any one or mixtures of two or more selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof. Examples of halides thereof include, but are not limited to, fluoroethylene carbonate (FEC).
[0093] Specific examples of linear carbonate compounds that can be used include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more of these.
[0094] Among carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate are high-viscosity organic solvents with high dielectric constants, and can more effectively dissociate lithium salts in the electrolyte. When such cyclic carbonates are mixed in a suitable ratio with linear carbonates with low viscosity and low dielectric constants such as dimethyl carbonate and diethyl carbonate, an electrolyte solution with higher electrical conductivity can be produced.
[0095] As the ether among the organic solvents, any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, and ethyl propyl ether, or a mixture of two or more of these, can be used, but is not limited thereto.
[0096] Of the organic solvents, the ester may be any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, α-valerolactone, and β-caprolactone, or a mixture of two or more of these, but is not limited thereto.
[0097] The present invention will be described in more detail with reference to the following examples. However, the configurations described in the examples described in this specification are merely examples of the present invention and do not represent all of the technical ideas of the present invention, and therefore there may be various equivalents and modifications that can replace them at the time of filing this application.
[0098] <Example>
[0099] <Example 1> Cathode active material (LiNi 0.8 Co 0.1 Mn 0.1O2 (NCM811), conductive material (carbon black), and binder (Polyvinylidene fluoride, PVDF) were mixed in a weight ratio of 96:2:2 into N-Methyl-2-Pyrrolidone (NMP) and mixed to prepare a positive electrode slurry. The positive electrode slurry was then applied to a 12 μm thick aluminum foil as a positive electrode current collector, and the positive electrode current collector was charged to 3.1 mAh / cm. 2 The positive electrode was prepared by coating with 100% water.
[0100] Artificial graphite, conductive material (carbon black), and binder (Polyvinylidene fluoride, PVDF) were mixed in a weight ratio of 96:2:2 into N-Methyl-2-Pyrrolidone (NMP) to prepare anode slurry. The prepared anode slurry was applied to a 10 μm thick copper foil as a cathode current collector to obtain a current of 3.1 mAh / cm. 2 The negative electrode was prepared by coating with 100% water.
[0101] Then, a radiation solution containing PVDF-HFP (LBG from Arkema, HFP content 5%) was applied at 0.7 g / m 2 The porous web was then subjected to electrospinning at a loading of 190° C. and a pressure of 20 kgf / cm to form a porous web made of ultrafine fibers. 2 A separation membrane having a thickness of 14 μm was produced by applying heat and pressure under the specified conditions.
[0102] Then, a separator was interposed between the positive and negative electrodes to prepare a jelly-roll type electrode assembly. The electrode assembly was inserted into a battery case, and an electrolyte was injected and the battery case was sealed to prepare a cylindrical secondary battery with a diameter of 21 mm. The electrolyte was prepared by adding LiPF6 at a concentration of 1.4 M to an organic solvent of 20:20:60 (volume ratio) of ethylene carbonate (EC), ethylmethylcarbonate (EMC) and dimethylcarbonate (DMC). Vinylene carbonate (3 vol%) and succinonitrile (1 vol%) were also mixed into the electrolyte.
[0103] The lithium secondary battery prepared as above was disassembled, and the negative electrode was punched out to a size of 23 mm x 120 mm, and the separator in contact with the negative electrode was punched out to a size of 20 mm x 120 mm to prepare a test specimen.
[0104] <Example 2> A test specimen was prepared in the same manner as in Example 1, except that the electrode of the test specimen was changed from the positive electrode to the negative electrode.
[0105] <Examples 3 to 4> In Examples 3 and 4, test specimens were prepared in the same manner as in Examples 1 and 2, except that the thickness of the separator was changed to 13 μm in Examples 1 and 2.
[0106] <Example 5> A test specimen was prepared in the same manner as in Example 2, except that the separator of the lithium secondary battery was changed to a polyethylene separator containing an acrylate-based binder mixture having a thickness of 14 μm.
[0107] Specifically, the acrylate-based binder mixture was prepared by adding an inorganic material (Al2O3, 97% by weight), an acrylate-based binder (SG-L02, 3% by weight, manufactured by GL Chem) and a fluorine-based nonionic surfactant (FC4430, 3M, 0.001% by weight) to water as a solvent and stirring the mixture until the total amount of the inorganic material and the acrylate-based binder was 100% by weight.
[0108] <Example 6> A test specimen was prepared in the same manner as in Example 5, except that the lithium secondary battery prepared in Example 5 was subjected to an activation process. Specifically, the activation process included an initial charge step (SOC, 3%), high temperature aging (60°C, 4 hours), and a degassing step including room temperature aging (12 hours). After additional charging to SOC 65% in the room temperature aging step, a full charge to SOC 100% (4.2V) and a discharge step to SOC 0% (2.5V) were performed.
[0109] <Examples 7 to 8> In Examples 7 and 8, test specimens were prepared in the same manner as in Examples 5 and 6, except that the thickness of the separator was changed to 13 μm in Examples 5 and 6.
[0110] <Comparative Example>
[0111] <Comparative Example 1> Artificial graphite, conductive material (carbon black), and binder (Polyvinylidene fluoride, PVDF) were mixed in a weight ratio of 96:2:2 into N-Methyl-2-Pyrrolidone (NMP) to prepare anode slurry. The prepared anode slurry was applied to a 10 μm thick copper foil as a cathode current collector to obtain a current of 3.1 mAh / cm. 2 The negative electrode was prepared by coating with 100% water.
[0112] Then, a radiation solution containing PVDF-HFP (LBG from Arkema, HFP content 5%) was applied at 0.7 g / m 2The porous web was then subjected to electrospinning at a loading of 190° C. and a pressure of 20 kgf / cm to form a porous web made of ultrafine fibers. 2 A separation membrane having a thickness of 14 μm was produced by applying heat and pressure under the specified conditions.
[0113] Then, the separator was laminated on the surface of the negative electrode, and pressed at 90°C and 200 kgf for 40 seconds using a heat press to bond the negative electrode and separator. Then, the negative electrode was punched out to a size of 23 mm x 120 mm, and the separator adjacent to the negative electrode was punched out to a size of 20 mm x 120 mm to prepare a test specimen.
[0114] <Comparative Example 2> LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive material (carbon black), and binder (Polyvinylidene fluoride, PVDF) were mixed in a weight ratio of 96:2:2 into N-Methyl-2-Pyrrolidone (NMP) and mixed to prepare a positive electrode slurry. The positive electrode slurry was then applied to a 12 μm thick aluminum foil as a positive electrode current collector, and the positive electrode current collector was charged to 3.1 mAh / cm. 2 The positive electrode was prepared by coating with 100% water.
[0115] Then, a radiation solution containing PVDF-HFP (LBG from Arkema, HFP content 5%) was applied at 0.7 g / m 2 The porous web was then subjected to electrospinning at a loading of 190° C. and a pressure of 20 kgf / cm to form a porous web made of ultrafine fibers. 2 A separation membrane having a thickness of 14 μm was produced by applying heat and pressure under the specified conditions.
[0116] Then, the separator was laminated on the surface of the negative electrode, and pressed at 90°C and 200 kgf for 40 seconds using a heat press to bond the negative electrode and separator. Then, the negative electrode was punched out to a size of 23 mm x 120 mm, and the separator adjacent to the negative electrode was punched out to a size of 20 mm x 120 mm to prepare a test specimen.
[0117] <Comparative Examples 3 to 4> In Comparative Examples 3 and 4, test specimens were prepared in the same manner as in Comparative Examples 1 and 2, except that the thickness of the separator was changed to 13 μm in Comparative Examples 1 and 2.
[0118] <Comparative Example 5> A test specimen was prepared in the same manner as in Comparative Example 1, except that the separator was changed to a polyethylene separator containing an acrylate-based binder mixture having a thickness of 14 μm.
[0119] Specifically, the acrylate-based binder mixture was prepared by adding an inorganic material (Al2O3, 97% by weight), an acrylate-based binder (SG-L02, 3% by weight, manufactured by GL Chem) and a fluorine-based nonionic surfactant (FC4430, 3M, 0.001% by weight) to water as a solvent and stirring the mixture until the total amount of the inorganic material and the acrylate-based binder was 100% by weight.
[0120] <Comparative Example 6> A test specimen was prepared in the same manner as in Comparative Example 5, except that the thickness of the separator was changed to 13 μm.
[0121] <Experimental Example>
[0122] 1) Measurement of adhesion between electrodes and separators in dry or wet conditions The interfacial adhesion between the electrodes and the separators of the test specimens of Examples 1 to 4 and Comparative Examples 1 to 4 was measured using a UTM (LLOYD Instrument LF Plus) device.
[0123] Specifically, in Examples 1 to 4, the test specimens were fixed to a fixture supporting an electrolyte, and the test specimens were supported in the electrolyte so that the electrolyte could be impregnated into the test specimens for about 1 hour, and then the interfacial adhesion between the electrodes and the separator was measured. Meanwhile, in Comparative Examples 1 to 4, the test specimens were fixed to a fixture not supporting an electrolyte, and the interfacial adhesion between the electrodes and the separator was immediately measured.
[0124] The separation membrane of the test specimen of Examples 1 to 4 and Comparative Examples 1 to 4 fixed on the fixture was fixed to the grip of the UTM equipment, and the UTM equipment was operated to pull one side of the separation membrane at 100 mm / min to measure the force at which the separation membrane peeled off from the electrode. At this time, the measurement angle between the electrode and the separation membrane was 90°.
[0125] At this time, three test specimens were prepared for each of Examples 1 to 4 and Comparative Examples 1 to 4, and the adhesive strength of each test specimen was measured by the above-mentioned 90° peel-off test, and the average value was calculated. The results are shown in FIG. 7.
[0126] As shown in FIG. 7, the average adhesive strength between the anode and separator of Comparative Example 1 prepared through a dry bonding process was about 63 gf / 20 mm, whereas the average adhesive strength between the anode and separator of Example 1 prepared through a wet bonding process was about 0.5 gf / 20 mm.
[0127] In addition, the average adhesive strength between the positive electrode and separator of Comparative Example 2 prepared through a dry bonding process was about 141 gf / 20 mm, whereas the average adhesive strength between the positive electrode and separator of Example 2 prepared through a wet bonding process was about 5 gf / 20 mm.
[0128] This is because a dry adhesion process in which the electrolyte is not wetted improves the adhesive strength between the negative electrode and the separator, whereas a wet adhesion process in which the electrolyte is wetted reduces the adhesive strength between the negative electrode and the separator. It can be seen that the interfacial adhesive strength between a positive electrode or a negative electrode supported in an electrolyte, as in the inside of an actual secondary battery, and a separator is significantly different from the interfacial adhesive strength between a positive electrode or a negative electrode and a separator prepared without being wetted by the electrolyte.
[0129] Therefore, it is necessary to evaluate the interfacial adhesion between the electrode and the separator in an environment wetted with an electrolyte under the same conditions as inside an actual secondary battery. The results of measuring the interfacial adhesion between the electrode and the separator in a wetted state with an electrolyte, which mimics the conditions inside an actual secondary battery, can increase the reliability of predicting changes in the adhesion between the electrode and the separator that occur inside an actual secondary battery.
[0130] Meanwhile, referring to FIG. 7, the average adhesive strength between the anode and separator of Comparative Example 3 prepared through a dry bonding process was about 40 gf / 20 mm, whereas the average adhesive strength between the anode and separator of Example 3 prepared through a wet bonding process was about 3 gf / 20 mm.
[0131] In addition, the average adhesive strength between the positive electrode and separator of Comparative Example 4 prepared through a dry bonding process was about 71 gf / 20 mm, whereas the average adhesive strength between the positive electrode and separator of Example 4 prepared through a wet bonding process was about 4 gf / 20 mm.
[0132] In Examples 3-4 and Comparative Examples 3-4, only the thickness of the separator was changed from Examples 1-2 and Comparative Examples 1-2, and the adhesive strength between the negative electrode or positive electrode and the separator was measured under the same conditions. It can be confirmed that Examples 3-4 and Comparative Examples 3-4, in which the separator is relatively thin, are subjected to less gravity than Examples 1-2 and Comparative Examples 1-2, in which the separator is relatively thick, and that the adhesive strength between the electrode and the separator is relatively small. In other words, it can be confirmed that Comparative Examples 3-4, which have undergone a dry adhesion process, show a large difference in the magnitude of adhesive strength when compared with Examples 3-4, which have undergone a wet adhesion process.
[0133] As a result, even if the thickness of the separator is changed, there is a large deviation in the adhesion strength measurement results between the electrode and the separator under conditions where the electrolyte is not wetted and conditions where the electrolyte is wetted. Therefore, it is necessary to measure the adhesion strength between the electrode and the separator under conditions where the electrode is wetted with the electrolyte, similar to the inside of an actual secondary battery. This can improve the reliability of predicting whether or not the separator will fold inside an actual secondary battery.
[0134] 2) Measurement of adhesion between electrode and separator at each process step The interfacial adhesion between the electrodes and the separators of the test specimens of Examples 5 to 8 and Comparative Examples 5 to 6 was measured using a UTM (LLOYD Instrument LF Plus) device.
[0135] Specifically, in Examples 5 and 7, a test specimen obtained by disassembling a lithium secondary battery that had not undergone an activation process was fixed in a receiving portion of a fixture containing an electrolyte, and the test specimen was supported in the electrolyte for about 1 hour so that the electrolyte could be impregnated into the test specimen, and then the interfacial adhesion between the negative electrode and the separator was measured. Meanwhile, in Examples 6 and 8, a test specimen obtained by disassembling a lithium secondary battery that had undergone an activation process was supported in a fixture containing an electrolyte as in Examples 5 and 7, and then the interfacial adhesion between the negative electrode and the separator was measured. Meanwhile, in Comparative Examples 5 and 6, a test specimen was fixed in a receiving portion of a fixture not containing an electrolyte, and the interfacial adhesion between the negative electrode and the separator was immediately measured.
[0136] The separators of the test specimens of Examples 5 to 8 and Comparative Examples 5 to 6, which were fixed to the fixture, were fixed to the grips of the UTM equipment, and the UTM equipment was operated to pull one side of the separator at 100 mm / min to measure the force at which the separator peeled off from the negative electrode. At this time, the measurement angle between the electrode and the separator was 90°.
[0137] At this time, three test specimens were prepared for each of Examples 5 to 8 and Comparative Examples 5 to 6, and the adhesive strength of each test specimen was measured by the above-mentioned 90° peel-off test, and the average value was calculated. The results are shown in FIG. 8.
[0138] 8, the average adhesive strength between the negative electrode and separator of Comparative Example 5 prepared through a dry bonding process was about 14.5 gf / 20 mm, whereas the average adhesive strength between the negative electrode and separator of Example 6 prepared through a wet bonding process and prepared by disassembling a lithium secondary battery that had not been subjected to an activation process was about 1.5 gf / 20 mm. Meanwhile, the average adhesive strength between the negative electrode and separator of Example 6 prepared through a wet bonding process and prepared by disassembling a lithium secondary battery that had been subjected to an activation process was about 4.5 gf / 20 mm.
[0139] As confirmed in the above-mentioned Experimental Example 1, the dry adhesion process improves the adhesive strength between the anode and the separator, but the wet adhesion process in which the electrolyte is wetted reduces the adhesive strength between the anode and the separator. It can be confirmed that the interfacial adhesive strength between the anode and the separator supported in the electrolyte, as in the inside of an actual secondary battery, is significantly different from the interfacial adhesive strength between the cathode or anode and the separator prepared without being wetted with the electrolyte.
[0140] Therefore, there is a need to evaluate the interfacial adhesion between the negative electrode and the separator under wet conditions that mimic the conditions inside an actual secondary battery, thereby increasing the reliability of predictions of the adhesion between the electrode and the separator that occurs inside an actual secondary battery.
[0141] Meanwhile, when examining the adhesive strength behavior of Example 5 prepared by disassembling a lithium secondary battery that did not undergo an activation process and Example 6 prepared by disassembling a lithium secondary battery that underwent an activation process, it can be seen that Example 6 exhibits higher adhesive strength than Example 5. This is believed to be due to the fact that the interfacial adhesive strength between the anode and the separator was improved due to various factors through the step-by-step charge / discharge process, aging process, and degassing process.
[0142] Furthermore, the adhesive strength between the electrode and the separator is measured under wet conditions for test specimens manufactured from lithium secondary batteries manufactured under different conditions for each stage of the activation process of the secondary battery. Based on the measurement results, it is possible to predict the behavior of the adhesive strength between the electrode and the separator inside the secondary battery according to various conditions for each stage of the activation process, and to prevent the folding phenomenon of the separator at each activation process stage.
[0143] 8, the average adhesive strength between the negative electrode and separator of Comparative Example 6 prepared through a dry bonding process was about 3.5 gf / 20 mm, whereas the average adhesive strength between the negative electrode and separator of Example 7 prepared through a wet bonding process and prepared by disassembling a lithium secondary battery that had not been subjected to an activation process was about 0.9 gf / 20 mm. Meanwhile, the average adhesive strength between the negative electrode and separator of Example 8 prepared through a wet bonding process and prepared by disassembling a lithium secondary battery that had been subjected to an activation process was about 1.3 gf / 20 mm.
[0144] Examples 7-8 and Comparative Example 6 were obtained by measuring the adhesive force between the negative electrode and the separator by changing only the thickness of the separator from Examples 5-6 and Comparative Example 5. Examples 7-8 and Comparative Example 6, which have a relatively large thickness, show similar behavior to the adhesive force results in Examples 5-6 and Comparative Example 5, except that they have relatively higher adhesive force than Examples 5-6 and Comparative Example 5, respectively. That is, Comparative Example 6, which has undergone a dry adhesion process, has a significant difference in the magnitude of adhesive force, unlike Examples 7-8, which have undergone a wet adhesion process. As described above in Examples 5-6 and Comparative Example 5, the adhesive force measurement results between the electrode and the separator under the condition where the electrolyte is not wetted and the condition where the electrolyte is wetted have a large deviation, so that it is necessary to measure the adhesive force between the electrode and the separator under the condition where the electrolyte is wetted, as in the case of an actual secondary battery, and thus the reliability of prediction of whether or not the separator will fold in the actual secondary battery can be improved.
[0145] Furthermore, Example 8, which was prepared by disassembling a secondary battery that had undergone an activation process, exhibited higher adhesion than Example 7, which was prepared by disassembling a secondary battery that had not undergone an activation process. This is also expected to be due to the improved adhesion between the negative electrode and the separator caused by various factors in the activation process. Meanwhile, when comparing the adhesion behavior with Examples 5 to 6, which had different separator thicknesses, it can be seen that the thicker the separator, the greater the difference in adhesion between the presence and absence of an activation process.
[0146] Accordingly, it has been confirmed that the adhesive strength between the negative electrode and the separator varies depending on whether or not the electrolyte is wetted, and also varies depending on whether or not the secondary battery that has undergone an activation process is disassembled, and also varies depending on the thickness of the separator. Therefore, by measuring the adhesive strength between the negative electrode and the separator by setting not only the electrolyte wetting conditions but also the activation process conditions and the thickness of the separator to be the same as those in an actual secondary battery, it is possible to improve the reliability of prediction of the adhesive strength between the negative electrode and the separator in secondary batteries actually manufactured under various conditions based on the results. [Explanation of symbols]
[0147] 1: Adhesive force measuring device 10: Fixture 11: Storage unit 12: 1st fixing protrusion 13: First guide groove 14:Second fixing protrusion 15: Second guide groove 20: Adhesive strength measuring device 21: Grip 30: Measurement specimen 31: Electrode 32: Separation membrane 40: Lid 41: Hinge
Claims
1. a fixture having a space for placing a test piece including an electrode and a separation membrane, and for containing an electrolyte in the space and fixing the test piece supported by the electrolyte; and an adhesion strength measuring device that has a grip for holding an end region of the separation membrane of the test specimen, and pulls the held separation membrane in a direction perpendicular to the surface of the electrode to measure a force with which the separation membrane is separated from the electrode, A part of an upper surface of the fixing jig is recessed downward to form a receiving portion for receiving the electrolyte, The test piece is supported in the electrolyte solution contained in the container, and an adhesion strength measuring device is configured to measure an interfacial adhesion strength between the electrode and the separator in a wet state.
2. 2. The adhesive strength measuring device according to claim 1, wherein the fixing jig has a structure including a lid for sealing an open portion of the container so as to prevent the electrolyte contained in the container from volatilizing.
3. the fixing jig includes a first fixing protrusion formed on an upper surface thereof by protruding upward and bending inward, and a first guide groove formed between a bottom surface of the first fixing protrusion and an upper surface of the fixing jig, 3. The adhesive strength measuring device according to claim 2, wherein a cover is inserted into the open end of the first guide groove in a sliding manner, and the open space of the receiving part is sealed or opened / closed.
4. the receiving portion includes a second fixing protrusion formed on a side surface thereof so as to protrude inward, and a second guide groove formed between a bottom surface of the second fixing protrusion and a bottom surface of the receiving portion, the second fixed protrusions and the second guide grooves each include a pair of second fixed protrusions and a pair of second guide grooves that are arranged facing each other in a width direction of the accommodating portion, 4. The adhesive strength measuring device according to claim 1, wherein the test piece is inserted into the open ends of the pair of second guide grooves in a sliding manner.
5. The adhesion measuring device according to claim 4, wherein the storage section is structured such that the ratio of the length between the pair of second fixed protrusions to the widthwise length of the area in which the second fixed protrusions are not formed is in the range of 0.7 to 0.
85.
6. 5. The adhesive strength measuring device according to claim 4, wherein the accommodation portion has a structure in which a length in a width direction of a region in which the second guide grooves are not formed is greater than a length between the pair of second guide grooves.
7. The adhesive strength measuring device according to claim 2 , wherein the fixing jig is connected to a cover by a hinge so that the open space of the receiving part is sealed or opened / closed by rotating the cover.
8. The adhesive strength measuring device according to claim 1 , further comprising a detector for detecting and displaying a force at which the electrode of the test specimen and the separation film are separated from each other.
9. 4. An adhesion measuring method, comprising: measuring an interfacial adhesion between the electrode and the separation membrane in a wet state, using the adhesion measuring device according to claim 1.
10. placing the test specimen in the fixture containing the electrolyte, and supporting the test specimen in the electrolyte; fixing an end of the separator of the test specimen supported in the electrolyte to a grip of an adhesive strength tester; 10. The method of claim 9, further comprising: operating the adhesion strength tester to separate the electrode and the separator of the test specimen supported in the electrolyte, and measuring an interfacial adhesion strength between the electrode and the separator in a wet state.
11. The method for measuring adhesive strength according to claim 10, wherein the test specimen includes a positive electrode or a negative electrode and a separator obtained by disassembling a secondary battery.
12. The adhesive strength measuring method according to claim 11 , wherein the electrolytic solution has the same components as the electrolytic solution stored inside the disassembled secondary battery.
13. The adhesive strength measuring method according to claim 11 , wherein the secondary battery is a secondary battery that has undergone an activation process.
14. The step of placing the test specimen in the fixture containing the electrolyte and supporting the test specimen in the electrolyte includes:
11. The adhesive strength measuring method according to claim 10, wherein a double-sided adhesive tape is attached to a surface of the electrode of the test specimen, and the test specimen attached to the glass substrate with the double-sided adhesive tape attached to the surface of the glass substrate is supported in the electrolyte.
15. The step of placing the test specimen in the fixture containing the electrolyte and supporting the test specimen in the electrolyte includes: The adhesive strength measurement method according to claim 10, further comprising a step of covering the electrolyte contained in the fixing jig with a lid to prevent the electrolyte from volatilizing during a waiting time for the test specimen supported in the electrolyte to be impregnated with a sufficient amount of electrolyte.
Citation Information
Patent Citations
Method for detecting adhesion strength of coating diaphragm of lithium ion battery
CN110132842A
Apparatus for pouring electrolyte in capacitor
KR1020120069830A
Mobile underwater surveillance system
KR1020240052308A
Apparatus for measuring peel strength of battery part using electromagnet and peel strength measurement method using the same
US20210080377A1